Conservation of Mahout Local Wisdom Based on Green Tourism - Opal Rungsimuntuchat, โอปอล์ รังสิมันตุชาติ; Tipaporn Posrie, ทิพาพร โพธิ์ศรี; เดือนโฮ้ง, ภาณุรังษี; สัมฤทธิตานนท์, ลลิตา (Dusit Thani College Journal, 2018)
This article’s aimed to conserve mahout local wisdom along with the natural environment by utilising activities in mahout training program of Thailand Elephant Conversation Center National Elephant Institute - Thai Elephant Conservation Center. The article is based on the study which has its objective to combine the conservation of the mahout local wisdom and tourism, leading to sustainable growth of tourism business. Analysis of the data collected from interviews given by experts from the mahout training school and the Thailand elephant conservation center pointed out the abilities and knowledge that make up the mahout local wisdom which were 1) elephants’ nutrition 2) elephants’ behaviours 3) making elephants training equipment 4) training elephants 5) bathing elephants and 6) building elephant pens. Using these aspects of mahout local wisdom, tourism activities can be organized, such as “Route of Khua Sa Ba” activity which was corresponding to the elephant bathing local wisdom and “Growing grass activities” activity which was corresponding to the elephant nutrition local wisdom. These activities help conservation of mahout local wisdom and opening new windows for tourism.